The Effect of Fraud Pentagon on Fraudulent Financial Statement of Banking in Indonesia - Dewi, Mega Arisia (Faculty of Economic and Business, 2021)
This study aims to determine the effect of financial targets, financial stability, external pressure, effective monitoring, nature of industry, change in auditors, rationalization, change of company directors, CEO’s Picture on fraudulent banking financial statements in Indonesia for 2014-2019. This study uses the dependent variable, namely fraudulent financial reporting, while the independent variables are financial targets, financial stability, external pressure, effective monitoring, nature of industry, change in auditors, rationalization, competence and arrogance. The show that the variable financial targets, change in auditors, change of directors and CEO’s picture have no effect on the detection of fraudulent financial statements. Meanwhile, financial stability, external pressure, ineffective monitoring, nature of industry, and rationalization have an effect on the detection of fraud in financial reports for 2014-2019. The results of this study provide an understanding for the public and the general public that the government’s efforts so far have always played a major role in maintaining the condition of the Indonesian economy in order to avoid attempts to cheat financial statements.